1995
DOI: 10.1136/pgmj.71.834.211
|View full text |Cite
|
Sign up to set email alerts
|

Fractional excretion of potassium in normal subjects and in patients with hypokalaemia

Abstract: SummaryThe aim of our study was the determination of fractional excretion of potassium (FEK+) in both normal subjects and hypokalaemic patients. Three hundred and twelve normal subjects aged 21-69 years and 84 hypokalaemic patients aged 36-72 years were studied. The mean FEK+ in normal subjects was 8% (range 4-16%). FEK' was positively correlated with serum potassium (r = 0.74, p < 0.0001) and inversely with serum creatinine (r = -0.51, p < 0.001). The mean FEK' in patients with hypokalaemia of extrarenal ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 5 publications
5
71
1
5
Order By: Relevance
“…In several cases, multiple plasma magnesium values were available; in these cases, to avoid bias, we quote the median value together with time-matched plasma calcium, phosphate, albumin, and, when available, PTH levels. Renal magnesium and calcium excretion were assessed in patients with hypomagnesemia, and hypermagnesuria was defined as a fractional magnesium excretion Ͼ4% 45,46 and hypocalciuria as a fractional calcium excretion Ͻ1%. 47 Statistical significance between parameters with discrete values was determined using Fisher exact test and Mann-Whitney U test.…”
Section: Cohort Detailsmentioning
confidence: 99%
“…In several cases, multiple plasma magnesium values were available; in these cases, to avoid bias, we quote the median value together with time-matched plasma calcium, phosphate, albumin, and, when available, PTH levels. Renal magnesium and calcium excretion were assessed in patients with hypomagnesemia, and hypermagnesuria was defined as a fractional magnesium excretion Ͼ4% 45,46 and hypocalciuria as a fractional calcium excretion Ͻ1%. 47 Statistical significance between parameters with discrete values was determined using Fisher exact test and Mann-Whitney U test.…”
Section: Cohort Detailsmentioning
confidence: 99%
“…The urinary electrolyte values revealed sodium excretion was 402 mEq/L, chloride was 281 mEq/L and potassium was 41.8 mEq/L per 24 h. The urinary Ca/creatinine ratio was low at 0.04 mg/mg (N ≥ 0.2) [8]. The fraction excretion of potassium (FE K ) was 29.4% (N = 4-16%, mean value 8%) [9] and high transtubular potassium gradient (TTKG) suggested that renal potassium wasting was responsible for the hypokalemia [10]. This findings indicated that the patient might have had renal tubulopathy and prompted us to examine distal tubular function.…”
Section: Sinaga Et Almentioning
confidence: 97%
“…Dette betyr at s-magnesium ikke er en optimal prøve i vurdering av magnesiummangel. Magnesium i spoturin og estimering av fraksjonert magnesiumekskresjon i urin kan gi informasjon om årsak, mens døgnutskil-lelse av magnesium i urin, som er praktisk vanskelig å gjennomføre i sykehjem og heller ikke ble gjennomført i sykehus i vårt tilfelle, sannsynligvis er en bedre parameter for evaluering av hypomagnesemi (14,15).…”
Section: Noe å Laere Avunclassified